Multi-objective Non-linear Programming Method of Optimizing Foundation Deformation Modulus for Jinping High Arch Dam - Hui Peng; De-fu Liu; Bin Tian (2009 International Joint Conference on Computational Sciences and Optimization : 24-26 April 2009, 2009)
The good deformation characters of foundation are severely requested when a high dam especially high arch dam is constructed on the foundation. But it doesn't mean the higher modulus the better working condition of arch dam. It is a big difficult problem for designers to rationally make a design which not only does well to the stress, stability and deformation for arch dam, but also can save a large sum of money on treating foundation through man-made methods. This paper establishes an optimization model for multi-objective non-linear programming of deformation modulus for arch dam foundation based on the unit deformation modulus method for calculating the stress of arch dam. In the optimization model, the deformation modulus E which varies with different elevation for arch dam foundation is chosen as design variable and through using multi-objective non-linear programming method the optimal deformation modulus is solved which on the one hand avails the best working condition of arch dam and on the other can reduce the treatment costs to the minimum within the value bound of deformation modulus that artificial methods can reach. The model created in this paper is used to solve the optimal deformation modulus of Jinping arch dam, the tallest high arch dam both in China and in the world. The calculated results indicate that the optimization model is reasonable and practical and also provides strong technique support to designers and foundation treatment.